Effect of formamidinium/cesium substitution and PbI2 on the long‐term stability of triple‐cation perovskites - Shukla, Shashwat (2020)
Altering cation and anion ratios in perovskites has been an excellent avenue in tuning the perovskite properties and enhancing the performance. Recently, MA/FA/Cs triple cation mixed halide perovskites have demonstrated efficiencies reaching up to 22 %. Similar to the widely explored MAPbI3, excess PbI2 is added in these perovskite films to enhance the performance. Previous reports demonstrate that the excess PbI2 is beneficial for the performance. However, not much work has been conducted about its impact on stability. Triple cation perovskites (TCP) deploy excess PbI2 up to 8 %. Thus, it is imperative to analyze the role of excess PbI2 in the degradation kinetics. In this paper, we have varied the amount of PbI2 in the triple cation perovskite films and monitored the degradation kinetics by X-ray diffraction (XRD) and optical absorption spectroscopy. We found that the inclusion of excess PbI2 adversely affects the stability of the material. Faster degradation kinetics is observed for higher PbI2 samples. However, excess PbI2 samples showed superior properties such as enhanced grain sizes and better optical absorption. Thus, careful management of the PbI2 quantity is required to obtain better stability and alternative pathways should be explored to achieve better device performance rather than adding excess PbI2.